Herbicide options for weed control in dry-seeded aromatic rice in India - Mahajan, Gulshan; Chauhan, Bhagirath S. (Cambridge University Press, 2013)
The looming water crisis and shortage of labor during rice transplanting in northwest India have led researchers to develop alternative methods to transition away from puddled transplanted rice. In this context, dry-seeded rice (DSR) is emerging as an efficient production technology to replace puddled transplanted rice. Weeds, however, are the main biological constraints to its success. A study comprising 12 treatments was conducted to evaluate the efficacy of PRE (pendimethalin and pyrazosulfuron) and POST herbicides (bispyribac, penoxsulam, and azimsulfuron) applied either alone or in a sequence for weed control in dry-seeded fine rice cv. ‘Punjab Mehak 1’. Results indicated that the single application of pendimethalin (750 g ai ha−1) PRE, pyrazosulfuron (15 g ai ha−1) PRE, bispyribac-sodium (25 g ai ha−1) POST, penoxsulam (25 g ai ha−1) POST, and azimsulfuron (20 g ai ha−1) POST reduced total weed biomass by 75, 68, 73, 70, and 72%, respectively, compared with the nontreated control at flowering stage of the crop. Azimsulfuron POST and pyrazosulfuron PRE proved effective against purple nutsedge and crowfootgrass, respectively. Chinese sprangletop, large crabgrass, and junglerice were effectively controlled with pendimethalin PRE. POST application of bispyribac-sodium and penoxsulam provided effective control of rice flatsedge. Compared to the nontreated control, grain yield following the single application of pendimethalin PRE, pyrazosulfuron PRE, bispyribac-sodium POST, penoxsulam POST, and azimsulfuron POST increased by 149, 119, 138, 124, and 144%, respectively. The sequential application of herbicides proved better than single applications. The lowest weed biomass was observed with the sequential application of pendimethalin PRE followed by azimsulfuron POST, and rice yielded 228% more than the nontreated control following this treatment. The results of this study are important for farmers growing DSR in making decisions regarding the application of POST herbicides, according to existing weed flora in the field.